Exposure to air pollution and non-neoplastic digestive system diseases: findings from the China health and retirement longitudinal study - Kou, Yanqi; Du, Shenshen; Du, Weiwei; Ye, Weixiang; Yang, Yuping; Qin, Ling (Frontiers in Public Health, 2024)
ObjectivesIncreasing concern about air pollution’s impact on public health underscores the need to understand its effects on non-neoplastic digestive system diseases (NNDSD). This study explores the link between air pollution and NNDSD in China.MethodsWe conducted a national cross-sectional study using 2015 data from the China Health and Retirement Longitudinal Study (CHARLS), involving 13,046 Chinese adults aged 45 and above from 28 provinces. Satellite-based spatiotemporal models estimated participants’ exposure to ambient particulate matter (3-year average). An analysis of logistic regression models was conducted to estimate the association between air pollutants [particulate matter with a diameter ≤ 2.5 μm (PM2.5) or ≤10 μm (PM10), sulfur dioxide (SO2), nitrogen dioxide (NO2), ozone (O3), and carbon monoxide (CO)] and NNDSD. Interaction analyses were conducted to examine potential modifiers of these associations.ResultsThe prevalence of NNDSD among participants was 26.29%. After adjusted for multivariate factors, we observed a 6% [odd ratio (OR) = 1.06, 95% confidence interval (CI): 0.94, 1.19], 23% (OR = 1.23, 95% CI: 1.09, 1.38), 26% (OR = 1.26, 95% CI: 1.12, 1.41), 30% (OR = 1.30, 95% CI: 1.16, 1.46), 13% (OR = 1.13, 95% CI: 1.01, 1.27) and 27% (OR = 1.27, 95% CI: 1.13, 1.43) increase in NNDSD risk with an interquartile range increase in PM2.5 (23.36 μg/m3), PM10 (50.33 μg/m3), SO2 (17.27 μg/m3), NO2 (14.75 μg/m3), O3 (10.80 μg/m3), and CO (0.42 mg/m3), respectively. Interaction analyses showed that PM2.5, SO2, and O3 had stronger effects on NNDSD risk among older adults, highly educated individuals, smokers, and married people, respectively.ConclusionThis study demonstrates that long-term exposure to PM2.5, PM10, SO2, NO2, O3, and CO is positively associated with NNDSD risk in Chinese adults aged 45 and above. Implementing intervention strategies to enhance air quality is essential for reducing the burden of NNDSD.